The Effect of Audit Findings, Local Government Losses, and Follow-up of Audit Recommendations on the Public Services Quality Through the Audit Opinion of Local Government Financial Statements in Sulawesi - Saipuloh, Saipuloh; Ismail, Tubagus; Adha, Wahyu Maulid (AIBPM Publisher, 2023)
With the existence of local governments and regional autonomy, the provision of public services will be of higher quality because local governments are close to communities throughout Indonesia. Several factors can influence the quality of public services provided by local governments, such as audit findings, local government losses, follow-up on audit recommendations, and audit opinions on Local Government Financial Statements (LGFS). The purpose of this study is to analyze the direct and indirect effects of audit findings, local government losses, and follow-up on audit recommendations on the quality of public services in Sulawesi in 2020-2021, with the audit opinion of LGFS as an intervening variable. The research analysis method used was SEM-PLS. The results found that audit findings have no significant effect directly on the audit opinion of LGFS and public service quality. Local government losses have a direct negative effect and are significant for the audit opinion of LGFS and the quality of public services. Follow-up on audit recommendations has a positive and significant effect on the audit opinion of LGFS and the quality of public services. The audit opinion of LGFS has no significant effect on the quality of public services. The audit opinion of LGFS is unable to mediate the indirect effect between audit findings, local government losses, and follow-up on audit recommendations on the quality of public services.